A Highly‐Efficient Type I Photosensitizer with Robust Vascular‐Disruption Activity for Hypoxic‐and‐Metastatic Tumor Specific Photodynamic Therapy. Issue 23 (6th May 2020) - Chen, Dapeng; Yu, Qing; Huang, Xuan; Dai, Hanming; Luo, Tao; Shao, Jinjun; Chen, Peng; Chen, Jie; Huang, Wei; Dong, Xiaochen
Abstract: Hypoxia severely impedes photodynamic therapy (PDT) efficiency. Worse still, considerable tumor metastasis will occur after PDT. Herein, an organic superoxide radical (O2 ∙− ) nano‐photogenerator as a highly effcient type I photosensitizer with robust vascular‐disrupting efficiency to combat these thorny issues is designed. Boron difluoride dipyrromethene (BODIPY)‐vadimezan conjugate (BDPVDA) is synthesized and enwrapped in electron‐rich polymer‐brushes methoxy‐poly(ethylene glycol)‐b‐poly(2‐(diisopropylamino) ethyl methacrylate) (mPEG‐ PPDA) to afford nanosized hydrophilic type I photosensitizer (PBV NPs). Owing to outstanding core–shell intermolecular electron transfer between BDPVDA and mPEG‐PPDA, remarkable O2 ∙− can be produced by PBV NPs under near‐infrared irradiation even in severe hypoxic environment (2% O2 ), thus to accomplish effective hypoxic‐tumor elimination. Simultaneously, the efficient ester‐bond hydrolysis of BDPVDA in the acidic tumor microenvironment allows vadimezan release from PBV NPs to disrupt vasculature, facilitating the shut‐down of metastatic pathways. As a result, PBV NPs will not only be powerful in resolving the paradox between traditional type II PDT and hypoxia, but also successfully prevent tumor metastasis after type I PDT treatment (no secondary‐tumors found in 70 days and 100% survival rate), enabling enhancement of existing hypoxic‐and‐metastatic tumor treatment. Abstract : A type I photosensitizer (PBV NP) with excellent O2 ∙− photogeneration ability is devised. Triggered by acidic tumor microenvironment, vadimezan, a vascular disrupting agent, can be effectively released from PBV NPs, facilitating the shut‐down of tumor vasculature. Harnessing the effective vadimezan release and O2 ∙− generation of PBV NPs, excellent hypoxic‐tumor ablation is achieved without any metastasis occurrence during the whole life‐span of mice .